Terpenoids from the leaves of Podocarpus gracilior - Faiella, Laura; Temraz, Abeer; Siciliano, Tiziana; De Tommasi, Nunziatina; Braca, Alessandra (Phytochemistry letters, 2012)
Three terpenoids, 2α,16-dihydroxy-4β-carboxy-O-β-d-glucopyranosyl-19-nor-totarol, nagilactone K, and 15-hydroxy phaseic acid were isolated from the leaves of Podocarpus gracilior. Structures were elucidated by 1D and 2D NMR spectroscopy as well as by mass spectrometry analysis. [Display omitted] ► Nor- and bis-norditerpenes are interesting cytotoxic metabolites of Podocarpus genus. ► They are considered chemotaxonomic markers for the genus. ► The phytochemical study of P. gracilior leaves was performed. ► Three new terpenoids, including two diterpenes, were identified. Three new terpenoids, 2α,16-dihydroxy-4β-carboxy-O-β-d-glucopyranosyl-19-nor-totarol (1), nagilactone K (2), and 15-hydroxy phaseic acid (3), together with nine known compounds, were isolated from the leaves of Podocarpus gracilior. Their structures were determined by means of 1D and 2D NMR spectroscopy as well as by mass spectrometry analysis.